REPRESENTASI PERILAKU MENYIMPANG INCEST DALAM SERIAL ANIMASI YOSUGA NO SORA DI SITUS INTERNET - Adam Pratama Putra; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
represent the deviant behavior of incest, which is a blood relationship that a family member does with other family members. The animation of Yosuga no Sora has the pros and cons of the release in Japan as well as in Indonesia because of the genre which is a distorted behavior. The purpose of this research was to see how the representation and meaning of the denotation, connotations, and mythical incest behavior deviates in the animation of Yosuga no Sora and how the animation of Yosuga no Sora represent incest deviant behavior.The study used qualitative research methods with the semiotic approach of Roland Barthes. The subjects used in this study were scenes contained in the animation of Yosuga no Sora and the objects in this study, namely the audio and Visual animation series Yosuga no Sora. The data collection techniques performed are documentation and library studies. The validity technique of the data in this study uses triangulation. The data Analysis unit raised in this study contained in 10 scenes.The first of these results is the meaning of the denotation, the connotations and the incest myths in the animated series Yosuga no Sora. Its denotations are the behavior of Haru and Sora in living their lives starting with each other's feelings, kissing, embracing, and having sex many times. The conjunction is their act as a twin brother in the face of each other's feelings in a blood bond like a jealous Sora when Haru approaches another girl, who does not give resistance even enthusiastically follows Haru's desire to have sex with her. The myth is the characteristic deviant behavior of incest that is forbidden in the law of Adat and religion among which is, in terms of adat is the wrong caterpillar, which is stated Hilman Hadikusuma in the Book of the Kuntara Raja Niti, namely doing adultery with siblings. In the view of religion, especially Islam, there is in Surah An-Nisa (4) verse 22-24 in this case it is in the sentence ' your foster-sisters '. They do it almost at all times and give unrest to the community. The second research result is on the animated series Yosuga no Sora represent incest devious behavior is kissing, hugs, alone without clothes, and having sex even after Haru is aware that their relationship is a Was wrong and was spotted by their friend, but they continued the relationship.